O abandono do trabalho docente em aulas de educação física: A invisibilidade do conhecimento disciplinar - González, Fernando Jaime (2013)
This research aimed to recognize similarities and differences in the configuration of cases of teachers of Physical Education characterized by dereliction of teaching. This study tried to understand how members of the school community, especially managers, see (if they do) the teaching practices of two teachers with similar teaching propositions in the classroom, but with a different engagement with the institution.The text was constructed based on two case studies developed in 2010 in public schools in counties of northeastern states of Rio Grande do Sul. Data were collected based on semi-structured interviews and field diaries.The results indicate that the neglect of teaching is perceived by members of the school community only when the teacher rejects any proposition in class and does not respond to other needs of the school, and his action is not acknowledged. The teacher is not guided by the contents of the higher education of the school discipline, and still does not change the school routines and minimally contemplates the tradition. The knowledge addressed (or not) in Physical Education classes is invisible to the eyes of school administrators